Implementation of Contextual Learning Improves the Lighting Installation Learning Outcomes of Students of SMKN 1 Tomohon - Calvin Mamahit; Herry Sumual; Eddy Kembuan; Fransiska Makaliwe (Department of Electrical Engineering Education, Faculty of Engineering, State University of Manado, 2024)
This study is expected to improve learning outcomes. Electrical lighting installation for grade XII students using a contextual learning model during the 2022–2023 academic year. The study was conducted in two cycles, with planning, implementation, action, observation/evaluation, and reflection as components of each cycle. This study involved 30 grade XII TITL students. The collected data were analyzed through test techniques. It was analyzed using qualitative descriptive techniques. The results of the study showed that the average student learning outcomes in cycle 1 in the electrical lighting installation component were 67.4% in the moderate category, which in cycle 2 increased to 80% in the high category, indicating an increase of 85.66%. Thus, the contextual learning model has been proven to improve the learning outcomes of grade XII TITL students at SMKN 1 Tomohon in the 2022–2023 academic year.